2013
DOI: 10.1186/1559-0275-10-6
|View full text |Cite
|
Sign up to set email alerts
|

Protein expression profiling of nuclear membrane protein reveals potential biomarker of human hepatocellular carcinoma

Abstract: BackgroundComplex molecular events lead to development and progression of liver cirrhosis to HCC. Differentially expressed nuclear membrane associated proteins are responsible for the functional and structural alteration during the progression from cirrhosis to carcinoma. Although alterations/ post translational modifications in protein expression have been extensively quantified, complementary analysis of nuclear membrane proteome changes have been limited. Deciphering the molecular mechanism that differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 52 publications
2
20
0
Order By: Relevance
“…Because of the limit on protein loading volumes, more abundant proteins in total protein gels often obscure some proteins of low abundance, although they become visible in subcellular protein gels. This is especially true for membrane-associated proteins, which are usually involved in intercellular protein-protein interactions (PPI) such as vector-pathogen interactions (Gu et al, 2003;Cordero et al, 2009;Khan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the limit on protein loading volumes, more abundant proteins in total protein gels often obscure some proteins of low abundance, although they become visible in subcellular protein gels. This is especially true for membrane-associated proteins, which are usually involved in intercellular protein-protein interactions (PPI) such as vector-pathogen interactions (Gu et al, 2003;Cordero et al, 2009;Khan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The comparative study on the differentially expressed subcellular proteomes between normal and pathological status of host has become one of the most effective strategies with respect to revealing the mechanism of pathogen infection and searching for specific biomarkers (Khan et al, 2013). The commonly studied subcellular proteomes include microsomal, mitochondrial and sometimes cytosolic proteins.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was reported that aberrant up‐regulation of LRRC1 contributes to human HCC . The nuclear membrane proteome of HCC showed that CYB5A protein was down‐regulated and played a role in oncogenesis of HCC . Our finding showed that up‐regulation of LRRC1 and down‐regulation of CYB5A were associated with tumor grade.…”
Section: Discussionmentioning
confidence: 49%
“…The functional association networks of the 16 chitin metabolism enzymes were generated using STRING 9.1 ( ). Since proteins are often involved in multiple cellular processes or metabolic pathways, these close interaction patterns, evident with high confidence score, are helpful for a better understanding of the activities of each individual protein when observed in a network of associations [ 31 ]. As illustrated in Figure 6 A, the highly conserved protein chitin synthase 1 (krotzkopf verkehrt, kkv) had high score (>0.9) with coexpression evidenced close relation to chitin deacetylase family CDA1 (serp), CDA2 (LCBP1), CDA4 (CG32499) and several other functional partners like obstA and Gasp which has chitin binding domain.…”
Section: Resultsmentioning
confidence: 99%